1987
DOI: 10.1103/physrevb.36.1969
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear-spin noise and spontaneous emission

Abstract: The spontaneous emission from nuclear spins has been observed at liquid-He temperatures. The spins, 'Cl nuclei, are placed in the inductor of a tuned LCR circuit coupled to a dc superconducting quantum interference device used as a radio-frequency amplifier. 'When the spins are saturated and have zero polarization, the emission is observed at the nuclear quadrupole Larmor frequency as a bump in the spectral density of the Nyquist noise current in the tuned circuit. This bump arises from the temperature-indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0
9

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 13 publications
2
82
0
9
Order By: Relevance
“…This conclusion is consistent with the finding of the authors of Ref. [13] that the fluctuation-dissipation theorem predicts a temperature-independent injection of spin noise from a system of spins 1/2 into a resonant circuit. Since the contribution of vacuum fluctuations to d I z /dt is proportional to I z , however, the net rate of spontaneous emission is temperature dependent.…”
Section: B Equation Of Motion For I Zsupporting
confidence: 82%
See 1 more Smart Citation
“…This conclusion is consistent with the finding of the authors of Ref. [13] that the fluctuation-dissipation theorem predicts a temperature-independent injection of spin noise from a system of spins 1/2 into a resonant circuit. Since the contribution of vacuum fluctuations to d I z /dt is proportional to I z , however, the net rate of spontaneous emission is temperature dependent.…”
Section: B Equation Of Motion For I Zsupporting
confidence: 82%
“…Since the time constant for spontaneous emissions by a nuclear spin into free space is many orders of magnitude larger than the time available for NMR experiments [12], however, spontaneous emission normally makes a negligible contribution to relaxation. Enhancing the emission rate by coupling spins to an inductive resonator has enabled the detection of emitted energy in macroscopic samples in the high-temperature limit [13,14], but the enhancement provided by the resonator still yielded relaxation time constants far too long to be relevant for NMR applications.…”
Section: Introductionmentioning
confidence: 99%
“…In yet another experiment, Sleator et al 86 observed "spin noise" in 35 Cl. An rf signal at the NQR frequency equalized the populations of the two nuclear spin levels, and then was turned off to leave a zero-spin state.…”
Section: E Magnetic Resonancementioning
confidence: 96%
“…Sleator et al (10,11) achieved the first experimental observation of nuclear spin noise by detecting a weak nuclear quadrupole resonance noise spectrum of a sample cooled to 1.5 K in a tuned circuit using a super conducting quantum interference device (SQUID) detector. These researchers related the phenomenon of spin noise to spontaneous emission being enhanced by the coupling to cavity modes (10, 11).…”
mentioning
confidence: 99%